Tactical behaviour of winning athletes in major championship 1500-m and 5000-m track finals - Aragón, Sonia; Lapresa Ajamil, Daniel; Arana, Javier; Anguera, María Teresa; Garzón, Belén (European Journal of Sport Science, 2017)
This article analyses the tactics employed by middle-distance (1500-m) and long-distance (5000-m) runners from an observational methodology perspective. The subject of investigation has received little attention from specialists in the field of athletics, with most research focusing on physiological studies of athlete performance. Using an ad hoc observation tool and a database containing systematically recorded data we detected time patterns (T-patterns) within the data recorded using the Theme software program (version 5.0), and analysed the tactics employed by winners of the men's 1500-m and 5000-m finals of the World Championships in Athletics [Edmonton 2001, Paris 2003, Helsinki 2005 (1500-m final only), Osaka 2007 (1500-m final only), Berlin 2009 and Daegu 2011], the European Athletics Championships (Munich 2002, Goteborg 2006, and Barcelona 2010) and the Olympic Games (Sydney 2000, Athens 2004, Beijing 2008 and London 2012). T-pattern detection and investigation of the relationship between category systems corresponding to the criteria comprising the observation tool revealed both similarities (starting lane and lane used during race, runner's position during race and sprint zone and lane) and differences (variations in pace, zones in which changes of pace occur, sprint initiation zone and winner's position at the start of the sprint) between the two disciplines.
Keywords: tactics; behaviour; performance; 1500-m; 5000-m; T-patterns; JCR; Scopus